An explicit spectral collocation method for the drug release coronary stents - Fakhri, Somayeh; Momeni-Masuleh, Sayed Hodjatollah (Mathematical modelling and analysis, 2022)
This research aims to solve a comprehensive one-dimensional model of drug release from cardiovascular stents in which the drug binding is saturable and reversible. We used the Lagrange collocation method for space dimension and the modified Euler method for time discretization. The existence and uniqueness of the solution, are provided. The consistency, stability, and convergence analysis of the proposed scheme are provided, to show that numerical simulations are valid. Numerical results accurate enough and efficient just by using fewer mesh.